Use several tests on the residual with control panel X to diagnose equation error models - Helaaa Abdulmajeed (College of Education for Pure Sciences, 2018)
In this research several models were matched of dynamic linear systems of the equation error models which included ARMAX and ARX  and applied using stationary  on a series of inputand output series. Then choice the best model based on statistical criteria AIC, FPE, Loss Function model was ARX. The second method using the intervention on a series of inputs and also to choices the best model based on statistical criteria AIC, FPE, Loss Function model was ARX. After that was the comparison between the ARX model using stationary and the ARX model using intervention based on several tests of the residual for both models, as well as test residual using one charts   control its quality.